Scientific Hypothesis: Essence, Types, and Methods of Verification - Abdulrhman, Yeza Abdulrhman Mesbah ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2021)
It is well-known that the experimental method has three steps: the research step, discovery stage, and the proof step. Since observation and experiment are the main components of the research step, scientific hypotheses are considered as a complement to these components. The reason for that is when we make observations and conduct experiments, we aim to reach the general principle or the law. As the verification of the validity of this hypothesis or that, it takes place in the proof step. After verification of the validity of the empirical hypothesis, it becomes a general law, and from this point of view, the scientific hypothesis is an essential element in the experimental method, as it represents the starting point in every experimental inference, and without it, it would not be possible to do any research, or acquire any knowledge. Therefore, the purpose of this study is to shed light on the scientific hypothesis and clarifies its form and its function in the experimental science, as well as stating the types of hypotheses and determining their conditions, and how to verify them.